Teachers' Pedagogic Competence in Strengthening Character Education of Students in Elementary Schools : Exploring Effective Strategies - Surtini, Surtini; Muhtar, Tatang (Jurnal Paedagogy, 2024)
This study aims to explore effective strategies for improving teachers' pedagogical competence to strengthen learners' character education at the primary school level. The research method used was a literature study with a qualitative approach. Primary and secondary data were obtained from books, documents, and journals that were of the same relevance as this research. After the data was obtained, the data analysis technique for this research used content analysis. The results of the study found that teachers must master educational technology to improve teaching effectiveness and student engagement. It involved using digital tools for assessment, teaching, and communication with students and parents. Teachers needed to develop 21st-century skills such as critical thinking, creativity, collaboration and communication. These skills were important to help students become individuals who are ready to face future challenges. Teachers should apply an adaptive pedagogical approach, tailoring teaching methods to students' individual needs, interests and abilities. It includes differentiated learning, formative assessment and the use of adaptive technology. Character education should be integrated in the curriculum by teaching universal and contextual values. A holistic approach, including project- and problem-based learning, is important to develop a strong student character relevant to modern challenges. Continuous professional training and development for teachers is key to ensuring they are up-to-date with best practices and innovations in education. This involves workshops, online courses, mentoring and collaboration within communities of practice. Modern assessment and reflection are important for monitoring student progress and evaluating teaching effectiveness. The use of formative and summative assessments, technology in assessment, and regular reflection by teachers and students can improve the quality of learning. Collaboration with parents, communities, educational institutions, government and non-profit organizations can strengthen character education and support teachers' pedagogical competencies.